Many-sided performance testing of Finnsheep rams - Puntila, M. -L. (Agricultural and Food Science, 1988)
Central performance testing of young rams has been conducted in Finland since 1975, in 1985—87 indoors as combined phenotype and 1/2-sib tests, which are the subject of this study. There were 100 individual boxes available, of which ca. 90 were annually used for Finnsheep (F). The rams were fed on concentrate diet (13.5 % DCP) ad lib. + hay. The test period was from 60 to 150 days of age. Feed intake (FI) was recorded daily, live weights (LW) fortnightly. At the end, MLD-areas were ultrasonically scanned, fleeces weighed, some linear body measurements taken, and fleshiness and wool quality scored. A total of 276 F rams were tested. They were progeny of 85 sires (2—4 half-brothers/sire). The means for all rams (30 selected rams) were: birth type 3.19 (3.18), rearing type 2.93 (3.01), age at start 64.3 (63.7) days, 60-day LW 19.5 (19.5) kg, 150-day LW 45.1 (47.6) kg, ADG 284 (312) g/d, FI 1.28 (1.34) kg/d, FE 4.49 (4.29) kg/kg gain, MLD-area 8.83 (9.63) cm2. There was considerable variation in the important traits (ADG, FI, FE, MLD-area), in spite of preselection. The phenotypic correlations of ADG with 150-d. LW, FI, Fl/kg gain and MLD-area were .61, .57, —.63 and .37, resp. (PC.001). Those of 150-d.LW with the last three traits were .59, —.15 NS and 0.44, resp.(P< .001). Selection for ADG, 150-d. LW, Fl/kg gain and MLD area in the performance test appeared to improve the value of offspring for meat production in F.